EFFECTIVE COMMUNICATION FOR DISTANCE LEARNING - Aria Nur Farida Muslicha (SIGEH ELT : Journal of Literature and Linguistics, 2021)
The purpose of this study was to determine effective communication for distance learning. Which is viewed from the presence, response, understanding information from lecturers, and use of student communication applications in effective communication for distance lectures. This research uses descriptive quantitative method. Data were collected by administering a questionnaire accompanied by the reasons for choosing the answer chosen. The data in this study were analyzed descriptively which was presented in the form of a round diagram to describe effective communication for distance learning for students of the Islamic Education study program at the Tarbiyah Muhammadiyah University of Tanjung Redeb. The results showed that the attendance of students on a predetermined class schedule was 92%. Judging from the student response from the presence of lecturers by 100%. In terms of the student's ability to understand information from the lecturer, 55%. And in terms of online communication applications that are easier to use by students who are learning distance, WhatsApp is 62%. This shows that the message delivered by lecturers in distance learning can be accepted by all students. And the use of WhatsApp as a communication application that is most widely used by students has helped to realize effective communication for long-distance lectures.